Autologous Platelet Rich Plasma (PRP) — A Treatment Modality of Neuropathic Ulcers in Leprosy Patients: An Interventional Study - Tejinder Kaur; Sahibpreet Kaur; Gurkim Kaur (JK Science)
Neuropathic ulcers are a result of trophic changes among leprosy patients amidst sensory loss. Use of Autologous platelet-rich plasma (PRP) in trophic ulcers is known to facilitate the restoration of metabolic processes, promotion of neo-angiogenesis, improvement of cellular metabolism, and activation of local immune responses. Our case series of 10 leprosy patients aimed to assess the efficacy and safety of PRP in healing trophic ulcers among leprosy patients. Our results, substantiating the previous studies, showed acceleration in the formation of granulation tissue and rapid reduction of ulcer volume after three weekly sessions of PRP treatment. No side effects were noted.